2020
DOI: 10.3390/nu12010189
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Mercury Level with the Risk of Depression According to Fish Intake Level in the General Korean Population: Findings from the Korean National Health and Nutrition Examination Survey (KNHANES) 2008–2013

Abstract: Mercury is a cumulative neurotoxic agent, exposure to high levels of which may increase the risk of psychiatric symptoms. The purpose of this study was to examine the associations between blood mercury and depression risk in Korean adults. We analyzed the Korean National Health and Nutrition Examination Survey (KNHANES) with 11,754 participants (male: 5834 female: 5920) aged ≥19 years from 2008 to 2013. The associations of blood mercury with risk of depression were estimated using multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Depression is an increasingly serious global mental health problem, resulting in a significant decline in physical function and quality of life but an increase in disease incidence and mortality. In 2017, about 17.3 million adults aged 18 and over in the United States experienced at least one episode of major depression, with a prevalence of about 7.1% ( 1 ). According to the “depression and other common mental diseases: global health estimates” released by world health organization (WHO) in 2017, the total number of patients with depression in the world was 322 million.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is an increasingly serious global mental health problem, resulting in a significant decline in physical function and quality of life but an increase in disease incidence and mortality. In 2017, about 17.3 million adults aged 18 and over in the United States experienced at least one episode of major depression, with a prevalence of about 7.1% ( 1 ). According to the “depression and other common mental diseases: global health estimates” released by world health organization (WHO) in 2017, the total number of patients with depression in the world was 322 million.…”
Section: Introductionmentioning
confidence: 99%
“…The insignificant associations observed among the participants with arthritis and dietary supplement intake might be explained in this same way. Fish consumption is commonly recognized as the primary source of methylmercury exposure, and a Korean study suggested that higher blood mercury was positively associated with the risk of depression (31). However, a metaanalysis study reported that high-fish consumption could reduce the risk of depression based on the data from the observational studies, and the findings remained significant in the cohort studies (32).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the results from the studies conducted outside Korea, the blood Hg concentration in the Korean population showed a relatively large difference. This could be inferred based on various studies on the correlation between the amount of fish consumed and Hg concentration in the body [ 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and a study reporting that Asians have higher fish consumption than other ethnicities [ 40 ]. In a report on the amount of seafood consumed by countries, Asian countries, including Korea, continue to rank high [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%